2022
DOI: 10.21511/im.18(3).2022.05
|View full text |Cite
|
Sign up to set email alerts
|

Business marketing activities in Ukraine during wartime

Abstract: The war in Ukraine dealt a crushing blow to the country’s economy. The relevance of the topic is due to the marketing ability to be an effective tool for restoring and developing business in Ukraine. The paper aims to define the state and prospects for developing business and its marketing component during the war in Ukraine. The research analysis demonstrates that the share of business representatives who completely or partially ceased their activities during the first three months of the war decreased from 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Problems and Perspectives in Management, Volume 20, Issue 4, 2022 http://dx.doi.org/10.21511/ppm.20 (4).2022. 28 The obtained value of the complex indicator for the selected two countries among the group of 23 countries, Ukraine and Romania, shows that the level of prevention of enterprise bankruptcy is 4.520 and 5.644, respectively. The importance of the obtained values lies in the ability of the bodies responsible for the state of business development in their countries to make timely and quick decisions on preventing the bankruptcy of enterprises and to develop appropriate management measures.…”
Section: Author Contributionsmentioning
confidence: 96%
“…Problems and Perspectives in Management, Volume 20, Issue 4, 2022 http://dx.doi.org/10.21511/ppm.20 (4).2022. 28 The obtained value of the complex indicator for the selected two countries among the group of 23 countries, Ukraine and Romania, shows that the level of prevention of enterprise bankruptcy is 4.520 and 5.644, respectively. The importance of the obtained values lies in the ability of the bodies responsible for the state of business development in their countries to make timely and quick decisions on preventing the bankruptcy of enterprises and to develop appropriate management measures.…”
Section: Author Contributionsmentioning
confidence: 96%
“…-телемаркетинг (телефонні дзвінки); -robocalling (автоматичні телефонні дзвінки); -текстові повідомлення; -електронні листи; -цільова онлайн-реклама; -взаємодія в соціальних мережах і публікації; -телевізійні рекламні ролики; -купонні оголошення; -пряма поштова розсилка; -листівки та роздаткові матеріали; -кіоски та стенди [11]. Як і всі останні інструменти просування туристичного продукту прямий маркетинг має свої переваги та недоліки.…”
Section: виклад основного матеріалу дослідження з повним обгрунтуванн...unclassified
“…However, studies on the impact of war on business inside Ukraine are almost nonexistent (Korneyev et al, 2022). Notwithstanding this, there is a study (Korneyev et al, 2022) on challenges to the crisis management of business marketing activities in wartime in Ukraine (including challenges such as low purchasing power of the population, sales affected by the unstable situation, departure of customers) with suggestions for how to adapt marketing to the immediate situation where long-term planning is not an option. Tomej et al (2023) have studied tourism business resilience in times of war during the first 3 months following the invasion of Ukraine, and they found that the organizational resilience of small and medium-sized tourism companies was a matter of the manager's personal resilience (p. 3).…”
Section: Literature Review On Business and War In Ukrainementioning
confidence: 99%